The importance of personal financial planning: a study of Maxis Berhad / Rohaida Rosman - Rosman, Rohaida (2011)
Based on AKPK’s report, they have assisted 53,000 individuals with debts totaling RM5 billion since 2006. It shows that, here in Malaysia, most of us are not wise in dealing and planning our own personal finance. Where in the past, the personal financial planning was not an issue but today, this matter has become one of the must-to-know issues. The reason is that most of the public has been living in the dark on how to manage their own personal finance and they eventually end up suffer with financial problems and some might even been declared bankrupt. Based on the findings, in summary, some might have consciousness in personal financial planning, but the consciousness on that matter does not seem to give any atomic impact to their attitudes towards personal financial planning. Meanwhile, financial knowledge has given more impact to an individual’s attitudes towards personal financial planning. The reason is that, those high conscious individuals may not making the right steps in planning for their personal finance if they do not have the knowledge on personal financial planning. Thus, this research is conducted to study the importance of personal finance among Maxis employees. Employees at Maxis come from all walks of life. Some of them have been working for more than 10 years. Therefore, basically, this research aims to determine how many percents of employees in Maxis have knowledge and consciousness in personal finance and how that will affect their way of managing their personal finance and are the way they manage their personal finance align with the knowledge and consciousness they claimed they have.